2011
DOI: 10.1111/j.1365-2524.2011.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient access to healthcare services and optimisation of self-management for ethnic minority populations living with diabetes: a systematic review

Abstract: What is known?d People from ethnic minority groups with diabetes have poorer access to healthcare services.d People from ethnic minority groups with diabetes have poorer reported self-management of diabetes.d Culturally adapted programmes may improve outcomes -glycaemic control and service uptake -for patients from ethnic minority groups.What the study adds d A broad and systematic review of studies using mixed methods points to persistent barriers in patient access and self-management of diabetes, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 56 publications
2
65
0
Order By: Relevance
“…Five recent systematic reviews have focused on resiliency and/or interventions targeting at vulnerable populations with a chronic condition 19,3841 . Two reviews assessed interventions aimed at improving some aspect of chronic diseases management in ethnic minorities 40,41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five recent systematic reviews have focused on resiliency and/or interventions targeting at vulnerable populations with a chronic condition 19,3841 . Two reviews assessed interventions aimed at improving some aspect of chronic diseases management in ethnic minorities 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Two reviews assessed interventions aimed at improving some aspect of chronic diseases management in ethnic minorities 40,41 . Wilson et al found that access to healthcare is hindered by healthcare providers’ limited awareness of the cultural practices and beliefs of patients 41 . Our review points to the relevance of including a cultural competence approach when working with minority populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have explored the effects of cultural and linguistic barriers which may compromise the quality of care delivered to members of ethnic minority groups with diabetes (Davies, 2006;Hill, 2006;Fleming and Gillibrand, 2009). Very little is known about how these barriers may operate in particular societies, and some service providers do not appear to appreciate the nature of these barriers or how they may prevent members of ethnic minority groups from receiving patient-centred diabetes care (Department of Health, 2001;Roberts, 2007;Wilson et al, 2012). A better understanding of these cultural issues may guide healthcare commissioners and clinical commissioning groups (CCGs) to reconfigure diabetes services in primary care, which may improve both care service engagement and outcomes in minority populations (NHS Health Scotland, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Such burden requires structured support from the health sector including quality multidisciplinary primary health care, participation in diabetes education and access to community support resources (Bodenheimer, Wagner, & Grumbach, 2002). Diabetes patients from ethnic minorities are vulnerable to experiences of sub-optimal care in the health system (Wilson et al, 2012). In Australia, at least a third of people newly diagnosed with diabetes are overseas born (Catanzariti, Faulks, & Waters, 2007) and many of these are from non-English speaking backgrounds (Thow & Waters, 2005).…”
Section: Introductionmentioning
confidence: 99%